Revitalisasi Gerbang Wisata Pasir Putih untuk Tingkatkan Daya Tarik Pengunjung - Arya Dirgantara; Mansyur, Mansyur; Aryadi, Armin; Adnan, Septi; Syajruddin, Syajruddin; Mubarak, Azhar Aras; Purnama, Haerul; Ode, Altafakur La; Syafar, Muh. Ismail; Yatjong, Isramyano (TENANG : Teknologi, Edukasi, dan Pengabdian Multidisiplin Nusantara Gemilang, 2025)
The refurbishment of the Pasir Putih Beach entryway was executed to augment the destination's allure and improve the visiting experience. This project employed a Participatory Action Research (PAR) methodology, engaging local communities, government entities, and stakeholders in the planning, execution, and assessment phases. The activities encompassed problem identification, design planning, validation, implementation, and evaluation. The redevelopment outcomes embody local character via traditional ornamental features, creative illumination, and ancillary amenities such informational displays and seating arrangements. The engagement of local communities enhanced their sense of ownership and generated economic prospects during and subsequent to the rehabilitation. The evaluation results indicated a rise in visitor numbers and satisfaction with the renovation efforts. This program enhanced the aesthetic, functional, and sustainable design of Pasir Putih Beach, solidifying its status as a premier destination in Kolaka Utara. This exercise illustrates that a participative approach can facilitate sustainable tourist development